THE IMPORTANCE OF ESTABLISHMENT AND DEVELOPMENT OF TOURISTIC COOPERATIVES IN THE ECONOMY OF RURAL AREAS OF SERBIA - Laban, Milena; Janković, Milena (Economics of Agriculture, 2021)
Rural tourism in Serbia and its development has positive effects on all aspects of rural development, both economic and social. The aim of this paperwork is to investigate the importance that touristic cooperatives in rural areas of Serbia, although relatively new in this area, have and can have on the overall development of rural areas. For the purpose of the research, an interview was conducted with the directors of the existing tourist cooperatives in Serbia. Based on the obtained data, it was determined that this form of cooperative association is necessary, not only because of the development of tourism in the countryside, but above all because of the survival of the Serbian village. The obtained data on the problems and limiting factors that cooperative members face in business can be a further basis for future research on the topic of rural development through the establishment and strengthening of tourist cooperatives.